ANALISIS STABILITAS DINDING PENAHAN DI RUAS JALAN NGANTANG KABUPATEN MALANG - Syaifullah, Syaifullah; Suhudi, Suhudi; Rasidi, Nawir (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Soil as construction material as well as the foundation of a construction land or structures such as dams, embankments, retaining walls, buildings and bridges. In every construction requires a specific requirement in terms of both strength and economically. This study aimed to analyze and plan for a stable retaining wall on the stability of the shift, the overthrow and the carrying capacity by using Gravity Type On Roads Ngantang Locations in Malang. Calculation of earth pressure calculated using Rankine theory. Stability Analysis Results Retaining Walls with Gravity Type Dimensions: Width top (B1) 0.50 m, base width (B2) of 2.00 m and a total height (H + D) 14.00 m, which then did not secure the stability of the overthrow ( 0.4 1.5). Results Budget Plan (RAB) in the calculation of total fees earned USD 839 855 542, the cost of any work (m3) Rp 1,566,164.181, job retention costs (m) USD 27,995,184.73. Keywords: Analysis, Dimensional, Gravity Type Retaining Walls